Living in an increasingly connected world: a framework for continental‐scale environmental science. Issue 5 (1st June 2008) - Peters, Debra PC; Groffman, Peter M; Nadelhoffer, Knute J; Grimm, Nancy B; Collins, Scott L; Michener, William K; Huston, Michael A
Abstract : The global environment is changing rapidly, as the result of factors that act at multiple spatial and temporal scales. It is now clear that local processes can affect broad‐scale ecological dynamics, and that broad‐scale drivers can overwhelm local patterns and processes. Understanding these cross‐scale interactions requires a conceptual framework based on connectivity in material and information flow across scales. In this introductory paper to Frontiers' Special Issue on Continental‐scale ecology in an increasingly connected world, we (1) discuss a multi‐scale framework, including the key drivers and consequences of connectivity acting across spatial and temporal scales, (2) provide a series of testable hypotheses, predictions, and an approach, and (3) propose the development of a "network of networks", which would take advantage of existing research facilities and cyberinfrastructure. This unique framework and associated technology will enable us to better forecast global environmental change at multiple spatial scales, from local sites to regions and continents.